POLITICAL IDEOLOGIES AS CONCEPTS’ SPHERES: POSSIBILITIES OF AN INTERDISCIPLINARY COGNITIVE-DISCURSIVE ANALYSIS - Яковлєв, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
Consideration of different possibilities and opportunities for researching ideologies as concepts’ spheres that is as a complex bundle of concepts of different types, together with distinct structures of concepts’ fields and interrelations between them is provided. Such an understanding of political ideologies would enable analysts to apply a cognitive-discursive research framework comprised of a number of different scientific disciplines: first and foremost is based on political science expert knowledge in the realm of political concepts and cognitive linguistics which actually harbors cognitive-discursive research framework; second – sociology and cognitive sciences, and the third – discourse analysis. Political ideologies as concepts’ spheres are methodologically defined using the morphological approach to ideologies developed by M. Freeden, which allows comparing the core-periphery structure of an ideology with the concept of carcass (framework) and its variables within the cognitive approach. Based on a number of illustrative examples, it is proved that in order to understand how ideologies influence the perception of people one needs to analyze spheres and fields of concepts as cognitive schemes. An application of discourse analysis to analyze both the levels and structures of the spheres of concepts, but also to trace the formation and practical use of the ideological cognitive schemes, is advocated. However it is suggested that social science component should be researched on its own, i.e. separately from the cognitive side of a given sphere of concepts in order to grasp the ways ideological discourses are perceived on cognitive level. The concept of «the political self» is also mentioned in the context of researching the process of political socialization which is inevitable influenced by a number of social and cognitive factors. An example of how literature studies can be applied to study ideologies and even form a typology of them is also provided, opening a door for further discussions and studies into possibilities of creating an interdisciplinary framework of researching political ideologies as spheres of concepts.